Ictiofauna de córregos de duas sub-bacias do médio rio Araguaia, Barra do Garças-MT - Lima, Priscilla Costa (2014)
The Neotropical ichthyofauna is the most richest and diverse from the planet. Local and regional processes influence its structure, promoting high micro-habitat and biological diversity. In this context, the studied region is a Stat Park, which biodiversity knowledge is very important. The aims from the present study were to realize a ichthyologic survey, compare the fish assemblages diversity, richness, abundance and composition with the environmental integrity index between two sub-basins drainages with headwaters that flows to Araguaia river (South) and Mortes river (North). The sample campaigns were realized during the year 2013 in the months of June to September, in 24 sample points. To delimit a reach of 50 m we used two block-nets of 5mm net mesh. Throughout each 10 m reach (0m, 10m, 20m, 30m, 40m, 50m), we registered the width, depth, current velocity a substrate. It was captured 5083 individuals belonging to 6 orders, 20 families, 52 genus and 78 fish species. The diversity, richness and fish abundance were higher in streams that flow to Mortes River. The fish abundance was higher in streams with lower environmental integrity index. The richness was higher in larger streams, with higher substrate diversity and lower environmental integrity index. Species composition was related to width, substrate diversity and with the environmental integrity index. The specie share degree among the sub-basins was 33% a five species were constant in more than 50% of the streams. Streams with lower geographical distances had higher species composition similarity. The main factors associated with the differences between the two sub-basins drainages maybe are due to geomorphological differences, each sub-basin had very peculiar characteristics. In addition, historical and biogeographical processes may be favored this distinction, as the ichthyofauna as the abiotic variables.